Effects of extended postpartum anoestrus period on reproductive performance of indigenous beef cattle raised on smallholder farms in Ghana: An overview - Obese, F.Y.; Darfour-Oduro, K.A.; Adu, E.K. (Ghanaian Journal of Animal Science, 2009)
Reproduction is a major component of the productive efficiency for a cow-calf system. One of the main factors affecting reproductive performance is the calving interval, which is directly influenced by postpartum anoestrus. Prolonged postpartum anoestrus is a major constraint to maintaining a 12 month calving interval in indigenous beef cows raised in smallholder farms in Ghana, contributing to economic loss to herd owners. The extended duration of postpartum anoestrus is caused mainly by poor nutritional status of cows and long periods of suckling by calves. These factors interfere with hypothalamic release of gonadothrophin releasing hormone (GnRH), provoking a marked suppression in pulsatile luteinising hormone (LH) release, and thus inhibit follicular development and function. Inadequate nutrition may also delay the resumption of ovulation in postpartum cows through reduction in circulating concentrations of insulin and insulin-like growth factor-I (IGF-I). Developing strategies to hasten the re-establishment of ovarian cyclicity postpartum through improved nutrition of cows, early weaning of calves and hormonal treatments should improve productive performance of tropical beef cows raised on smallholder farms.
Keywords: Cattle; Postpartum Anoestrus; Reproductive Performance; Smallholder Farm